Central serous chorioretinopathy: what we have learnt so far. (1st July 2015) - Wong, Kah Hie; Lau, Kin Pong; Chhablani, Jay; Tao, Yong; Li, Qing; Wong, Ian Y.
Abstract: Central serous chorioretinopathy (CSCR) is a common retinal cause of visual loss. The mainstays of management are observation, photodynamic therapy (PDT) and laser procedures. Over the past decade, there has been rapid development in the existing and novel imaging techniques, functional testing and management of CSCR. However, there is no convincing treatment designed for CSCR yet. In recent years, the advances in PDT, with various adjustments in fluence and verteporfin dosage, and the comparisons between different types of PDT for acute and chronic CSCR in recent studies have provided greater insights into the role of PDT in treating CSCR. Novel laser procedures, such as the diode micropulse laser, have shown comparable efficacy to conventional lasers without laser‐induced damage. Antivascular endothelial growth factor, which was originally developed for treating cancers, has emerged to be a potentially effective treatment for CSCR. The potential role of mineralocorticoid receptor antagonists in treating CSCR has provided greater understanding of the pathogenesis. Based on the relevant studies, mainly from the past decade, we discuss updates to the management of CSCR according to the risk factor modifications, pharmacological interventions, PDT and laser procedures and concluded that PDT is the current best option for CSCR.